Intermediate Java: 5 Projects. - Wassell, Shaun (linkedin.com, 2024)
This intermediate-level course empowers learners to apply their Java knowledge through the development of five practical applications, fostering real-world problem-solving skills and mastery of object-oriented programming concepts.